Dual-station pseudo-Doppler localization method based on particle filtering with stable distribution noise - shuang QIUTian; zhe QIYin (Tongxin xuebao)
Traditional pseudo-Doppler bearing estimation algorithm could accurately calculate the angle of arrival (AOA) with Gaussian noise and high signal to noise ratio (SNR), but it was less robust with stable distribution noise. To over-come these shortcomings, a dual-station pseudo-Doppler localization method based on the particle filtering was proposed. The method employed particle filtering approach to jointly estimate the AOA of both stations, then applied a non-linear mapping to acquire the source location, forming an int tion of AOA calculation and dual-station localization. Simula-tions demonstrate that when the characteristic exponent of the stable distribution is in a medium degree, for example a=1.4, the proposed method is much more robust than the traditional method in low SNR circumstances, while main-taining the estimation accuracy of the traditional method when SNR is high. When SNR equals 10 dB, the positioning accuracy of the proposed method is much higher than the traditional method with a＜1.9 .